Factors Related to The Implementation of Handover in Hospital Inpatient Rooms - Kartini, Kartini (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2024)
Handover is an oral communication of information about patients carried out by nurses at the change of shift. Inaccurate information in carrying out acceptance considerations can have a serious impact on patients. The aim of this literature review is to determine the factors associated with patient handover in hospital inpatient rooms. A literature search was carried out based on articles published between 2018-2023 according to the inclusion and exclusion criteria that had been determined using 1 data base, namely GoogleSchool. This literature search uses the PRISMA guideline in carrying out the screening process. From the search results, 2,420 articles were obtained. After carrying out the screening process, there were 3 articles that met the criteria and will be analyzed. Based on a study of 3 articles, it was found that the factors related to the implementation of patient handover in inpatient rooms in hospitals are: supervision, knowledge, peer support, communication, and organizational culture. Factors related to the implementation of handover patient consist of interna and external factors. It is hoped that hospitals will establish policies related to the management of handover patient in the form of standards and handover patient procedures that are applied in all hospital inpatient rooms, socialization and need supervision toward handover patient. As well as increasing nurses' knowledge through training. Keywords: factors, consideration, inpatient, hospital, nurse